Two-dimensional transition metal carbides as supports for tuning the chemistry of catalytic nanoparticles - Zhe Li (Nature Portfolio, 2018)
The performance of supported metal nanoparticle catalysts can be tailored by metal-support interactions, but their use in catalyst design is still challenging. Here, the authors develop two-dimensional transition metal carbides as platforms for designing intermetallic compound catalysts that are efficient for light alkane dehydrogenations.